Daily Egg Consumption Does Not Alter Cardiometabolic Parameters in Children Living in a Food Insecure Environment: A Pilot Study (P08-074-19). (24th October 2019) - Walker, Sam; Hawley, Aubree; Tacinelli, Angela; Baum, Jamie
Abstract: Objectives: To determine if daily egg consumption improves markers of cardiometabolic health and body composition in children living in a food insecure environment. Methods: Twenty children were recruited to participate in a 12-week dietary intervention. Each participant was required to consume two eggs per day, five days per week. Participates were either assigned to a food insecure: (FI; n  = 10; 7 male, 3 female; 10.1 ± 2.0 y; 38.0 ± 16.2 kg; 144.0 ± 16.8 cm) or food secure (FS; n  = 10; 7 female, 3 male; 9.8 ± 2.2 y; 38.6 ± 12.0 kg; 145.6 ± 14.0 cm) group. FI was determined using the USDA's six item Short Form Food Security Survey or if their family was enrolled in SNAP. Prior to beginning the study, participants and their families received nutritional counseling and educational materials regarding food preparation and egg consumption. Eggs were provided for each family member and families were provided monthly grocery assistance. Compliance was assessed monthly and parents had to return grocery receipts and 3-day food records. Data was collected at baseline, 4-, 8-, and 12-weeks. Fasting plasma and serum samples were collected at each visit and glucose and triglycerides were analyzed using commercially available kits. Height and weight were recorded at each time point and a dual-energy x-ray absorptiometry (DEXA) was performed at baseline and at 12-week. Data were analyzed via two-way ANOVA using Prism GraphPad version 8.0. Significance was set at P  < 0.05). Results: Habitual egg consumption had no effect on glucose or triglycerides in either FI or FS children. In addition, there was no change in height or weight over the 12-week intervention in either group. Though not significant, favorable improvements in body composition parameters were observed in FI and FS groups. Bone mineral content increased by an average 3.2% ± 1.9 in the FI group and of 4.2% ± 2.8 in the FS group. Fat free mass increased by 2.2 ± 5.0 in the FI group and 2.1% ± 3.1 in the FS group. Conclusions: The results of this pilot study indicate that habitual consumption of eggs for twelve weeks does not impact cardiometabolic parameters in either FI or FS children. However, a larger study population and longer intervention period are needed. NCT NCT03412825. Funding Sources: This study was funded by the American Egg Board/Egg Nutrition Center.